Advantages of co-education - Hanson, Boline (My University, 1906)
Introduction: Co-education, or the instruction of both sexes in the same schools and classes, is a characteristic feature of the public education in the United States. The same policy is being rapidly carried forth in other countries where it is advisable, but nowhere does it present so unique a feature as in our own country. The idea of co-education of the sexes is no new “fanged-doctrine.” It has passed the stage of being simply an experiment and is today giving to the world ample satisfaction. It has been found that woman is capable of contending with man in the higher paths of literature and science and that education refines and strengthens the mind of the woman as well as that of the man. The co-education of sexes is the natural, normal mode of education. One of the strongest arguments for the continuation together of the boys and girls in the whole course of education is the very fact that they are placed together in that first and best of all schools, the family, ‘they grow up in the same nursery, by the same fireside, praying together at the same mother's knee, and are blessed by the benediction of a common father'. The children of a neighborhood go to church together, to Sunday school together, on the streets they walk together, they play together. If the Divine Providence had desired the sexes to be trained separately, why has he not ordered all the children in one family girls and all those in another to be boys? President Fairchild of Oberlin College thus gives his testimony in favor of the co-education of the sexes in college life, after an observation of its results for thirty four years. "The ease with which the discipline of so large a school is conducted has not ceased to be a matter of wonder to ourselves. One thousand students are gathered from every class in society of every grade of culture the drat mass of them indeed bent on improvement, but numbers sent by anxious friends, with the hope that they may be saved or recovered from wayward tendencies; yet the disorders, incident to such gatherings are essentially unknown among us.
Citation: Hanson, Boline. Advantages of co-education. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Co-Education; Education; Schools; Theses